A cross-sectional survey of awareness of human papillomavirus-associated oropharyngeal cancers among general practitioners in the UK. Issue 7 (28th July 2018) - Lechner, Matt; Vassie, Claire; Kavasogullari, Cemal; Jones, Oliver; Howard, James; Masterson, Liam; Fenton, Tim; Yarbrough, Wendell; Waller, Jo; Gilson, Richard
Abstract : Objectives: To examine the level of awareness of the link between human papillomavirus (HPV) and oropharyngeal cancer (OPC) and epidemiological trends in HPV-related OPC among general practitioners (GPs) in the UK. Design: Cross-sectional survey. Participants: 384 GPs from England, Scotland, Wales and Northern Ireland. Setting: The survey was administered at GP training courses and via email to lists of training course attendees. Primary and secondary outcome measures: Proportion of respondents aware of the link between HPV and OPC; respondents' self-rated knowledge of OPC; proportion of participants aware of the epidemiological trends in HPV-associated OPC. Results: 384 questionnaires were completed with an overall response rate of 72.9%. 74.0% of participants recognised HPV as a risk factor for OPC, which was lower than knowledge about the role of smoking, chewing tobacco and alcohol consumption (all >90% recognition). Overall, 19.4% rated their knowledge of OPC as very good or good, 62.7% as average and 17.7% as poor or very poor. The majority (71.9%) were aware that rates of HPV-associated OPC have increased over the last two decades. Fewer than half (41.5%) of the participants correctly identified being male as a risk factor of HPV-associated OPC, while 58.8% were aware that patients with HPV-associated OPC tend to be younger than those with non-HPV-associated disease. Conclusions: The association of HPV infection with OPC is a relatively recent discovery. Although the level of awareness of HPV and OPC among GPs was high, the characteristics of HPV-associated OPC were less well recognised, indicating the need for further education.